Inhibitory Effect of Moringa Leaf Extract on Escherichia coli Isolated from Urine of UTI Patients - Daniela Tri Soge; Yoan Novicadlitha; Wilhelmus Olin; Norma Tiku Kambuno (Poltekkes Kemenkes Kupang, 2025)
The moringa plant (Moringa oleifera) are a well-known medicinal plant in Indonesia, often referred to as the “Miracle Tree” due to their numerous health benefits. Urinary Tract Infection (UTI) is a clinical condition in which bacteria are present in the urinary tract, typically caused by microorganisms such as Escherichia coli (E. coli). Moringa leaves contain antibacterial phytochemicals such as flavonoids, saponins, alkaloids, terpenoids, steroids, catechol tannins, gallic tannins, and anthraquinones, which can inhibit the growth of E. coli. UTIs are commonly treated with antibiotics, but excessive use of antibiotic can have consequence, such as antibiotic resistance. This study aims to determine the inhibitory activity of moringa leaf extract against E. coli isolated from the urine of UTI patients. The bacteria were cultured using EMBA media, Gram staining, and biochemical tests. The extract was prepared through maceration, and the Minimum Inhibitory Concentration (MIC) was determined using the broth dilution method. The MIC test used bacterial suspensions at McFarland 0,5 and 0,25 with extract concentrations of 0,25%, 0,5%, 1%, 5%, 10%, 20%, 30%, and 40%. Results were observed using the turbidimetry method or visual observation. The findings showed that moringa leaf extract inhibited E. coli growth at concentrations of 20%, 30%, and 40%, as the suspensions remained clear after incubation. Conclusion: Moringa leaf extract can inhibit E. coli growth isolated from UTI patient urine and may be recommended for UTI prevention and treatment. These results are expected to provide knowledge that moringa leaves can be processed as food ingredients that have the potential to be used in efforts to prevent UTIs.